Evaluación del rol de la vía nigroestriada en una respuesta de discriminación condicionada en ratas adultas: una revisión sistemática (2020)
Behavioral flexibility is a response related to the ability to regulate or modify conduct using environmental signals. This allows an adequate behavioral response, that faces a constant-changing environment. At the moment, there is extensive literature that considers the prefrontal cortex as the main structure responsible for this function. Still, basal ganglia and other sub-cortical structures are also involved in the ability to successfully adapt to the changes of the environmental contingencies. This review analyzes a series of experiments that assess the role of the rat nigrostriatal pathway in a conditional discrimination response based on temporal GABAergic inhibition, using muscimol and baclofen, and local anesthetics such as bupivacaine and tetracaine. Results show that the ventral striatum is involved in initial learning as well as in performance, and the dorsal striatum is strictly responsible for performance but not learning. Inactivation of the dorsolateral striatum enhances sensitivity to changes of the contingency and inactivation...